Hubungan Perilaku Merokok dengan Memori Jangka Pendek pada Remaja - Setianingsih, Setianingsih; Purnomo, Romadhoni Tri; Qotifah, Ninda Lilis; Murtono, Agus (TRIAGE Jurnal Ilmu Keperawatan, 2023)
Smoking behavior is a bad habit that is often encountered in everyday life. Considered as a problem that can interfere with the development of adolescents in the future and these changes affect the behavior of children in the community, besides that it can interfere with health and risk factors of a non-communicable disease. This is a problem throughout the world both developed and developing countries. This study aims to determine the relationship of smoking behavior with short-term memory in class X teenagers at SMK Muhammadiyah 1 Klaten Utara. This study uses a descriptive correlational design with a cross sectional approach. The population of this research is teenage boys (16-19 years). The research respondents were 135 students who were obtained by purposive sampling technique in accordance with the inclusion criteria in the study. Data collection instruments used questionnaires and digit span tests. Bivariate data analysis uses the Kendall Tau test. The results of this study averaged age of 61.43 years. The results showed moderate smoking behavior (34.1%), short-term memory in adolescents at SMK Muhammadiyah 1 Klaten Utara is weak memory (52.6%). Kendall Tau test results show there is a relationship between smoking behavior with short-term memory in adolescents p value 0.00 (p <0.05). The conclusion between smoking behavior has a relationship with short-term memory in adolescents at SMK Muhammadiyah 1 Klaten Utara. Keywords : Smoking Behavior, Short Term Memory, Teenagers